Observation of superconductivity in 1T′-MoS2 nanosheets. Issue 41 (12th October 2017) - Guo, Chenguang; Pan, Jie; Li, Hui; Lin, Tianquan; Liu, Pan; Song, Changsheng; Wang, Dong; Mu, Gang; Lai, Xiaofang; Zhang, Hui; Zhou, Wei; Chen, Mingwei; et al.
Abstract : Studies on the preparation and physical properties of phase-pure 1T′-MoS2 are still scarce although a 1T′ phase MX2 (M = Mo and W; X = Se and Te) has recently been reported to be a Weyl semimetal, a quantum spin Hall insulator, and a superconductor. Abstract : Studies on the preparation and physical properties of phase-pure 1T′-MoS2 are still scarce although a 1T′ phase MX2 (M = Mo and W; X = Se and Te) has recently been reported to be a Weyl semimetal, a quantum spin Hall insulator, and a superconductor. Herein, we report a perfect single-layer 1T′-MoS2 structure based on edge-sharing octahedra. Pure 1T′-MoS2 nanosheets were successfully prepared using LiMoS2 single crystals. The arrangement of zig-zag Mo–Mo chains in the 1T′-MoS2 layer evolved from that of parent Mo–Mo diamond-like chains in LiMoS2 crystals after the removal of all lithium ions. A well-defined 1T′-type lattice structure was observed and characterized by scanning transmission electron microscopy, X-ray photoelectron spectroscopy, and Raman spectroscopy. Surprisingly, superconductivity with an onset transition temperature ( T c ) of 4.6 K has been observed in the lithium-free 1T′-MoS2 nanosheets, which is not observed in semiconducting bulk or single-layer 2H-MoS2 .